MODEL SIMULASI PERKEMBANGAN, PERTUMBUHAN DAN NERACA AIR TANAMAN KENTANG PADA DATARAN TINGGI DI INDONESIA - Salwati, nFN (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2013)
This research aims to construct a simulation model of development, growth and waterbalance of potato crop. Reasearchalso predicts climate change impact on potato productivity in several potato production center in Indonesia. The cropmodel being constructed explains process mechanism of development and growth during crop life cycle as a responseto fluctuation of climatic. Three field experiments were conducted at three locations at Pacet and Galudra in West JavaProvince, and at Kerinci in Jambi Province, to support the model development; for model calibration (Pacet) and modelvalidation (Galudra and Kerinci). Paired t-test between model predictions of Granola variety with observations showedthat there were not significant differences (P> 0,05) on all variables tested, except leaf biomass. In Atlantic variety, therewere not significant differences (P> 0,05) on root, tuber biomass and soil water content. Based on graphical test showedcoefficient of determination were (R2) greater than 0,80 for all variables.Generally, results on validation suggested thatmodel predictions were not significantly different with field measurements at Galudra (Granola variety) and Kerinci(Atlantis and Granola variety) for variable of plant ages, biomass of root, stem, leaf and tuber, leaf area index, and soilwater content.Â